Requirement of LaeA, VeA, and VelB on Asexual Development, Ochratoxin A Biosynthesis, and Fungal Virulence in Aspergillus ochraceus - Wang, Gang; Zhang, Haiyong; Wang, Yulong; Liu, Fei; Li, Erfeng; Ma, Junning; Yang, Bolei; Zhang, Chenxi; Li, Li; Liu, Yang (Frontiers in Microbiology, 2019)
Aspergillus ochraceus is reported to be the major contributor of ochratoxin A (OTA), classified as one of the possible human carcinogen (group 2B) by the International Agency for Research on Cancer. The heterotrimeric velvet complex proteins, LaeA/VeA/VelB, have been most studied in fungi to clarify the relation between light dependent morphology and secondary metabolism. To explore possible genetic targets to control OTA contamination, we have identified laeA, veA and velB in A. ochraceus. Loss of laeA, veA and velB yielded mutants with differences in vegetative growth and conidial production. Especially, ΔlaeA almost lost the ability to generate conidiaphore under dark condition. The deletion of laeA, veA and velB drastically reduced the production of OTA. The wild type A. ochraceus produced about 1 μg/cm2 and 7 μg/cm2 OTA under light and dark conditions on media, while the three gene deletion mutants produced less than 20 ng/cm2 OTA, which was correlated with a down regulation of OTA biosynthetic genes. Pathogenicity studies of ΔlaeA, ΔveA and ΔvelB showed their reduction in disease severity in pears. Furthermore, 66.1% of the backbone genes in secondary metabolite gene cluster were significantly regulated, among which 81.6% were down regulated. Taking together, these results revealed that velvet complex proteins played crucial roles in asexual development, secondary metabolism and fungal virulence in A. ochraceus.